TINJAUAN HUKUM DAN KEBIJAKAN KAWASAN KONSERVASI LAUT (KKL) MUKIM IE MEULEE, KOTA SABANG: Suatu Implementasi Pengelolaan Perikanan Tangkap di Pulau Kecil - Yulianto, Irfan; Wiryawan, Budy; Mukminin, A (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2012)
The coastal area of Weh Island is divided into sub-districts (lhok) which are managed by traditional leader known as Panglima Laot. The Panglima Laot has the authority to regulate customary laws that aimed to bring social harmony and resolve conflicts concerning the marine resource use. In Anoi Itam and Ie Meulee of the east coast of Weh Island, the communities have high awareness toward the sustainable of the natural resources use, and this has led to the implementation of gear restrictions and no fishing zones regulations as part of their customary laws. These regulations have generated conflict with the other custom community, because the other custom community claimed that these existing customary regulations do not have legal base regulations. Gap analysis and analytical hierarchy process was used to analyze and describe the regulation that can be used as their optional regulation base. The result indicated that the Weh Island custom community had chosen a marine protected area that managed by community through Panglima Laot adopting regulations that recognised by local government. In the process of implementation, the determination area is a key priority (36.92%) followed by the establishment of management institutions (23.92%), financing (21.19%) and surveillance (17.94%).